Judge and punish: the penal state on trial - Lagasnerie, Geoffroy de (Stanford University Press, 2018)
Part one. What we are. The state on trial -- Subjects of the law : a repressive theory of power -- From law to critique -- Part two. The state and violence. Civilization and its lies -- See the state for what it is -- The double reality of violence -- Part three. The system of judgement. Beyond responsibility -- The politics of perceptions -- An individualizing narrative -- React differently -- Part four. The system of punishment. Accuse and punish -- The logic of punishment -- What is a crime? : the fictional frameworks of penality -- Penality, sovereignty, and democracy -- Part five. See the world : rethinking sociology